2020
DOI: 10.3390/nu12041093
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Vitamin D Supplementation in Obese Children During Integrated Weight–Loss Programme—A Double Blind Randomized Placebo–Controlled Trial

Abstract: Background: Vitamin D was studied in regards to its possible impact on body mass reduction and metabolic changes in adults and children with obesity yet there were no studies assessing the impact of vitamin D supplementation during a weight management program in children and adolescence. The aim of our study was to assess the influence of 26 weeks of vitamin D supplementation in overweight and obese children undergoing an integrated 12-months' long weight loss program on body mass reduction, body composition a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…As expected, we found that FM% at the end of the study was independently associated with VDD status of the included subjects. Previous studies showed similar results in term of BMI [ 27 ], while others suggested a dose-related effect on BMI, waist circumference, and total fat mass [ 28 ].…”
Section: Discussionmentioning
confidence: 56%
“…As expected, we found that FM% at the end of the study was independently associated with VDD status of the included subjects. Previous studies showed similar results in term of BMI [ 27 ], while others suggested a dose-related effect on BMI, waist circumference, and total fat mass [ 28 ].…”
Section: Discussionmentioning
confidence: 56%
“…Salehpour et al [ 121 ] presented inadequate data on the impact of VD 3 intake (25 μg as cholecalciferol) on glucose homeostasis in overweight or obese women with an average age of 38 ± 8 years old and a BMI of 29.9 ± 4.2 kg/m 2 . Brzezinski et al [ 122 ] observed an insignificant impact of 26-week VD (1200 IU) intake on body weight reduction in overweight and obese children aged 6–15 years old who had VD insufficiency (<30 ng/mL). Additionally, Jones et al [ 123 ] showed that supplementation of dairy (~700 mg per day of CAL with 500 kcal per day) and CAL-rich dairy (~1400 mg per day of CAL with 500 kcal per day) had no effect in increasing weight loss.…”
Section: Interrelationship Of Vd–cal In Obesity and Its Disease Statesmentioning
confidence: 99%
“…Two different continents in the same population also influenced the CAL concentrations [ 131 ]. Therefore, these variables may predominance the inadequate evidence of VD–CAL supplementation in obese populations [ 120 , 121 , 122 , 123 , 124 ].…”
Section: Interrelationship Of Vd–cal In Obesity and Its Disease Statesmentioning
confidence: 99%
“…Probiotic bacteria, mainly belonging to the genera Lactobacillus and Bifidobacterium , besides many health benefits, can produce vitamins ( 5 ) such as folate ( 6 ), and some other members of the gut microflora can produce cobalamin (B 12 ). Folic acid and vitamin B 12 are both required for normal cell division because of their involvement in DNA synthesis and amino acid metabolism.…”
Section: Introductionmentioning
confidence: 99%